(untitled) (The Research of Medical Science Review, 2025)
Objective: To determine the frequency of treatment success following the administration of folinic acid after methotrexate therapy in women with ectopic pregnancy. Methodology: This descriptive study was conducted at the Department of Obstetrics & Gynecology, Fatima Memorial Hospital, Lahore, over a six-month period from July 2024 to December 2024. A total of 100 women aged 20–40 years diagnosed with ectopic pregnancy (confirmed on transvaginal ultrasound with β-hCG >1000 mIU/mL) were enrolled via non-probability consecutive sampling. All participants received intravenous methotrexate (100 mg/m² bolus followed by 200 mg/m² infusion over six hours) along with folinic acid rescue (15 mg orally for four doses). Treatment success was defined as a spontaneous β-hCG drop below 100 mIU/mL and sonographic evidence of conception material evacuation within 48–72 hours.Results: Out of 100 participants, 92 (92%) achieved successful medical termination of ectopic pregnancy, while 8 (8%) required further management. No significant associations were found between treatment success and age (p = 0.392), BMI (p = 0.906), gestational age (p = 0.547), abortion history (p = 0.229), diabetes (p = 0.427), hypertension (p = 0.167), anemia (p = 0.119), previous ectopic pregnancy (p = 0.201), family history (p = 0.293), IVF status (p = 0.456), or socioeconomic status (p = 0.066). CONCLUSION: Folinic acid administration following methotrexate therapy is associated with a high success rate for medical management of ectopic pregnancy and is effective across diverse patient profiles. These findings support incorporating folinic acid as routine adjunct therapy to improve outcomes and reduce the need for surgical intervention.